(untitled) (Journal Of Educational and Psychological Researches, 2015)
Slow learning becomes a problem in the present , where it comprises ratio musnt ignore in every school . So , its one of education problems facing by parents and teachers . Slow learning subject regard of new subject attract the attention in the last years of the 20th century where the attention was focusing on the other disabilities but the existence of number of healthy children suffering from Learning problems attract the attention of the researchers . So , this study aims at recognizing the degree of self , concept among slow learner students and the differences significance of self concept according to sex and academic degree of parents variables. Because there is not tool , the researcher build a tool of self concept depending on the agreed scientific procedures of the validity and applied it on a sample consists of (zoo) male and female students in Baghdad at AL – kark and AL – Risafa sides . The researcher used the suitable statistical methods in the processing of information , where T.test of two independence samples to calculate the differences significance according to sex variable , T. test to find differences according to Academic degree of parents variable and scheffaes test for post hoc comparison to find differences in self concept according to different academic degrees of parents . The results show the slow learners have appositive self concept there are differences in self concept for female , and there are statistical significant differences for the higher degree the researcher Rogers Finally, the researcher concluded with some of recommendations and suggestions in the light of the results.